The Factors Related to the Caring Behavior of Clinical Nursing Students - Tintin Sukartini; Candra Panji Asmoro; Fiqih Ardi Pradana (Universitas Airlangga, 2019)
Introduction: The CB of clinical nursing students is very important but they are still in the implementation phase of the theory from when it was learned in college. This study aims to describe the correlation between intelligence quotient (IQ), emotional intelligence (EI) and spiritual intelligence (SI) with caring behavior (CB).Methods: This study was descriptive and correlational with a cross-sectional approach. The respondents of this research were all of the clinical nursing students (166 respondents) via the simple random sampling technique. The data was collected using questionnaires and analyzed using the Spearman-rho test with a level of significance ≤ 0.05.Results: The results showed that CB had a correlation with IQ (p=0.019, r=0.211), EI (p=0.048, r=0.178) and SI (p=0.000, r=0.456).Conclusion: IQ, EI, and SI have a correlation with CB. A higher quotient will produce a higher CB. Future research is expected to be able to analyze the other factors related to CB among clinical nursing students.